 # Homogeneous and Linear Differential Equations

• A differential equation which can be expressed in the form \frac{dy}{dx}=f(x,y)\ or\ \frac{dx}{dy}=g(x,y) where, f(x,y) and g(x,y) are homogenous functions of degree zero is called a homogeneous differential equation.
• If the homogeneous differential equation is in the form \frac{dx}{dy}= F(x, y) where, F(x, y) is homogeneous function of degree zero, then we make substitution \frac{x}{y}=v i.e., x = vy and we proceed further to find the general solution as discussed above by writing \frac{dx}{dy}=F(x,y)=h \left(\frac{x}{y}\right).
• A differential equation of the form \frac{dy}{dx}+Py=Q, where P and Q are constants or functions of x only is called a first order linear differential equation.

### Part7: View the Topic in this video From 00:13 to 10:36

Disclaimer: Compete.etutor.co may from time to time provide links to third party Internet sites under their respective fair use policy and it may from time to time provide materials from such third parties on this website. These third party sites and any third party materials are provided for viewers convenience and for non-commercial educational purpose only. Compete does not operate or control in any respect any information, products or services available on these third party sites. Compete.etutor.co makes no representations whatsoever concerning the content of these sites and the fact that compete.etutor.co has provided a link to such sites is NOT an endorsement, authorization, sponsorship, or affiliation by compete.etutor.co with respect to such sites, its services, the products displayed, its owners, or its providers.

•  \frac{dy}{dx} + P(x) y = Q(x) ⇒ If = e^{\int P(x) \ dx}
• \frac{dx}{dy} + P(y) x = Q(y) ⇒ If = e^{\int P(y) \ dy}
• d (x + y) = dx + dy
• d(xy) = y dx + x dy
• d\left(\frac{x}{y}\right)=\frac{y dx- x dy}{x^{2}}
• d (x2 + y2) = 2 (x dx + y dy)
• d\left(\frac{y}{x}\right)=\frac{x dy- y dx}{x^{2}}
• d\left(\log(xy)\right)=\frac{y dx+ x dy}{xy}
• d\left(\log\left(\frac{y}{x}\right)\right)=\frac{x dy - y dx}{xy}=\frac{-dx}{x}+\frac{dy}{y}
• d\left(\log\left(\frac{x}{y}\right)\right)=\frac{y dx - x dy}{xy}=\frac{dx}{x}-\frac{dy}{y}
• d\left(\tan^{-1}\left(\frac{y}{x}\right)\right)=\frac{x dy - y dx}{x^{2}+y^{2}}=\frac{\left(\frac{x dy - y dx}{x^{2}}\right)}{\left(1+\frac{y^{2}}{x^{2}}\right)}=\frac{d\left(\frac{y}{x}\right)}{1+\left(\frac{y}{x}\right)^2}
• d\left(\log(x^{2}+y^{2})\right)=2\left(\frac{x dx + y dy}{x^{2}+y^{2}}\right)
• d\left(\sqrt{x^{2}+y^{2}}\right)=\frac{x dx + y dy}{\sqrt{x^{2}+y^{2}}}
• d\left(\frac{-1}{xy}\right)=\frac{x dy + y dx}{x^{2}y^{2}}